Contract Law in E-Commerce Perspective and Its Implications for Consumers - Maulidiana, Lina; Idham, Idham; Nadriana, Lenny (IJBLE Scientific Publications Community Inc., 2025)
This research investigates contract law in the perspective of e-commerce and its impact on consumers. Facing digital transformation in the business world, particularly in the context of e-commerce, the contractual relationship between businesses and consumers becomes increasingly complex. The focus of this research involves exploring the legal implications arising from digital business transactions related to contract law in the e-commerce environment. The aim of this research is to provide insights into how contract law in e-commerce can affect the rights, obligations, and protection of consumers. The implementation of contracts in e-commerce, unlike conventional agreements, requires clear regulations regarding the validity and legal strength of these electronic contracts. In this research, a qualitative approach is employed using literature review and legal document analysis. Data is gathered from legal sources related to e-commerce and relevant previous research. The practical implications of this study are expected to provide a foundation for regulatory improvements and consumer protection in digital business transactions.